Type A1 but Not Type A2 Botulinum Toxin Decreases the Grip Strength of the Contralateral Foreleg Through Axonal Transport From the Toxin-Treated Foreleg of Rats - Yasushi Torii; Norio Akaike; Tetsuhiro Harakawa; Keiko Kato; Nakaba Sugimoto; Yoshitaka Goto; Shinji Nakahira; Tomoko Kohda; Shunji Kozaki; Ryuji Kaji; Akihiro Ginnaga (Elsevier, 2011)
Abstract.: The adverse effects of botulinum LL toxin and neurotoxin produced by subtype A1 (A1LL and A1NTX) are becoming issues, as the toxins could diffuse from the toxin-treated (ipsilateral) to contralateral muscles. We have attempted to produce neurotoxin from subtype A2 (A2NTX) with an amino acid sequence different from that of neurotoxin subtype A1. We measured the grip strength on the contralateral foreleg as an indicator of toxin spread from the ipsilateral to contralateral muscles. Doses of 0.30 log U or above of A1LL and A1NTX reduced the contralateral grip strength, whereas a dose of 0.78 log U of A2NTX was required to do so. We investigated the route of toxin spread using denervated, colchicine-treated, and antitoxin-treated rats. A1LL was transported via axons at doses higher than 0.30 log U and via both axons and body fluid at about 0.80 log U or a higher dose. Interestingly, A2NTX was transported via body fluid at about 0.80 log U or a higher dose, but not via axons to the contralateral side. It was concluded that A1LL and A1NTX decreased the grip strength of the toxin-untreated foreleg via both axonal transport and body fluids, while A2NTX was only transported via the body fluid. Keywords:: botulinum toxin, grip strength (rat), neurotomy, colchicine, axonal transport